Transport with different benzocaine concentrations and its consequences on hematological parameters and gill parasite population of matrinxã Brycon cephalus (Günther, 1869) (Osteichthyes, Characidae) - Falanghe Carneiro, Paulo César; Urbinati, Elisabeth Criscuolo; Martins, Maurício Laterça (My University, 2002)
The objective of this study was to evaluate the transport stressing effects and the different benzocaine concentrations on hematological parameters and parasite population of matrinxã Brycon cephalus (Osteichthyes, Characidae). Thirty fish (1.0 kg mean weight) were hauled in four 200-L plastic tanks for four hours, at different benzocaine concentrations (B0 = 0.0 g/L, B1 = 5.0 g/L, B2 = 10.0 g/L and B3 = 20 g/L). Before loading, blood and gills of 5 fish were collected. Other three samplings were performed after transport, and 24 and 96 hours later (recovery period). Blood cortisol, glucose, hematocrit, white cell differential count and the number of the gill parasite Piscinoodinium sp. were determined. Plasma cortisol increased in all treatments after transport, returning to initial levels 24 hours later. Blood glucose was also elevated after transport in all treatments, but only B0 and B1 fish recovered initial levels in 24 hours. B2 and B3 fish did not recover the initial levels until the end of the experimental period. After transport, the lymphocytes relative percentage decreased and the neuthrophils relative percentage increased, in all treatments. Ninety-six hours later, only B0 and B1 fish had recovered the initial levels of these parameters. The number of Piscinoodinium sp. on the gills of B3 fish was higher than in the other treatments 96 hours after transportation. The use of benzocaine did not mitigate stress responses and some negative effects were observed in fish transported with the highest concentrations.
Keywords: Benzocaine; Brycon cephalus; Matrinã; Stress; Transport